Penerapan Pendekatan PAIKEM (Aktif, Inovatif, Kreatif, Efektif dan Menyenangkan) pada Pembelajaran Pidato Persuasif: Suatu Kajian - Jeany Eva Krisna (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims: 1) To know how the application of active, innovative, creative, effective, and fun learning called PAIKEM in Indonesian language learning for class IX Semester 1 KD.4.4, namely "Pouring ideas, thoughts, directions, or messages in persuasive speech (living environment), social conditions, and methods or cultural diversity orally and/or in writing with due regard to structure and language ". The method of the research is qualitative research that focuses on the process. It directly observes the learning process of Indonesian in grade IX with the material "Delivering Persuasive Speeches". The result showed that the application of the PAIKEM (Active, Innovative, Creative, Effective and Fun) approach in the material of delivering persuasive speeches depended on the application of learning and teacher learning methods to motivate, foster curiosity, generate a sense of wanting to do, innovate, and be brave to issue an opinion from a student. Based on the results of this study, it is concluded that the process of learning speeches will be fun if it is supported by two things, namely students who always have a high enthusiasm for learning and teachers who always motivate students, teachers who understand students' learning conditions and teachers who can be accepted by students.